Wide awake surgery for flexor tendon primary repair: A literature review - Fulchignoni, Camillo (Orthop Rev (Pavia), 2020)
Flexor tendon injuries are extremely challenging conditions to manage for hand surgeons. Over the last few years enormous progress has been made for the treatment of these lesions with new surgical approaches being performed. One of these is the wideawake local anesthesia no tourniquet (WALANT) technique, also known as Wide Awake Technique that allows tendon repair under local anesthesia, enabling the tendon to move actively during surgery. Dynamic movement of the tendon during surgery is crucial for the orthopedic surgeon in order to understand if the tendon has been correctly repaired before leaving the operatory table. An electronic literature research was carried out on Pubmed, Google Scholars and Cochrane Library using ((Flexor tendon injury) OR (flexor tendon) OR (injury muscle tendon) OR (flexor pollicis longus tendon) AND ((wide awake repair) OR (wide awake) OR (wide awake hand surgery))as search terms. Authors believe that WALANT is an enormous add-on in the management of patients with flexor tendon injuries mainly because it allows direct visualization of the repair during flexion and extension movement of the fingers and also because it avoids general anesthesia or brachial plexus being more cost effective. The aim of these review was therefore to sum up the evidences available so far on the wade awake technique as an emerging treatment for patients with flexor tendon injuries.